Evaluation the Expression of Endoglin (CD105) & IL-3 Level of Pregnancy Women with Antiphospholipid Syndrome - Manal Salih (University of Thi-Qar Journal of Science, 2019)
This study designed to describe the histopathology changes of human placenta for pregnancies women with APAand normal pregnancies, also to estimate placental Immunohistochemical staining (IHC) expression patterns of endoglinin pregnancies with APA compared to normal pregnancies and quantify IL-3 serum level for both groups by usingELISA test. The histopathology results showed that arteries with degenerated media were associated with inflammatorycells and areas of hemorrhage were associated with moderate placentitis with inflammatory cells and fibrosis; alsocongested capillaries and blood vessels. The immunostaining results showed decrease in expression of endoglin in PASpregnancy compared than healthy pregnancy with significant difference (43.3% versus 75 % ; p ≤ 0.05) . Some arterieswith degeneration of sub region with hyalinization and congestion. The evaluation of the serum levels of IL-3 wereshowed the elevated level in healthy pregnancy (599.15 ±SE68.59 pg/ml) compared to APS pregnancy (264.96± SE38.28 pg/ml) with significant difference (P ≤ 0.05).